2017
DOI: 10.4038/sljch.v46i3.8329
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on medical comorbidities among children with autism spectrum disorder and controls in a children’s hospital

Abstract: Introduction: Autism spectrum disorder (ASD) is a neurodevelopmental disorder, in which medical disorders are known to occur higher than in the general paediatric population. This may indicate either that the neurodevelopmental disorder is acting as a risk factor or sharing a common pathophysiological mechanism with the medical disorder. We could not access any publications focusing on medical comorbidities in autism from Sri Lanka. Objective:To compare the prevalence and types of medical comorbidities between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Several medical comorbidities are also more common in individuals with ASD, such as epilepsy and gastrointestinal symptoms (Chandradasa et al, 2017). AEDs may be effective in managing seizures in this population; however, children with developmental disabilities may be at increased risk of negative side effects of these medications.…”
Section: Integrated Approaches For Addressing Common Comorbid Disordersmentioning
confidence: 99%
“…Several medical comorbidities are also more common in individuals with ASD, such as epilepsy and gastrointestinal symptoms (Chandradasa et al, 2017). AEDs may be effective in managing seizures in this population; however, children with developmental disabilities may be at increased risk of negative side effects of these medications.…”
Section: Integrated Approaches For Addressing Common Comorbid Disordersmentioning
confidence: 99%
“…Current research has identified maternal risk factors for ASD in conjunction with certain COCs. Recurrent maternal GI issues, hypertension during pregnancy, and gestational diabetes were found to significantly increase the risk of ASD and GI disorders (Chandradasa et al, 2017). Maternal psychiatric disorders have been found to be directly and in‐directly associated with a diagnosis of ASD and epilepsy (Ekinci et al, 2010; Jokiranta et al, 2014).…”
Section: Introductionmentioning
confidence: 99%